Significant Serum Progesterone Variations on the Day of Final Oocyte Maturation in Stimulated IVF Cycles - Shanker, Upma; Lawrenz, Barbara; Bungum, Leif; Depret Bixio, Leyla; Ruiz, Francisco; Coughlan, Carol; Fatemi, Human M. (Frontiers in Endocrinology, 2019)
Objective: To evaluate intraday serum progesterone levels on the day of final oocyte maturation in women undergoing ovarian stimulation in a GnRH-antagonist protocol. Study design, size and duration: Design: Prospective observational study. Setting: Private IVF center in Muscat, Oman. Patients: 30 patients with primary/secondary infertility and an indication for ovarian stimulation for IVF/ICSI treatment. The study was registered at the clinical trials.gov under the number: NCT03519776. Main outcome measures: Progesterone levels at 4 time points (8am, 11am, 2pm and 5pm) on the day of final oocyte maturation. Results: A total of 120 samples from 30 patients were included in this prospective study. Progesterone levels on the day of final oocyte maturation showed a significant decline over the day with the mean values at 8am: 1.03 ng/ml, at 11am: 0.81 ng/ml, at 2pm: 0.68 ng/ml and at 5pm: 0.64 ng/ml. The difference between the first and the last progesterone level was 0.39 ng/ml, reflecting a 37.8% decline of the progesterone level within 9 hours and there was a highly significant decrease in the progesterone levels recorded between 8am and 11am, between 8am and 2pm, between 8am and 5pm and 11am and 5pm (p < 0.001). Conclusion: The study findings have two clinically important conclusions: Firstly, progesterone levels on the day of final oocyte maturation decline significantly from the morning to the afternoon in patients, questioning the reliability of one arbitrarily taken progesterone level regarding the decision to perform a fresh embryo transfer or to cryopreserve the embryos. Secondly, declining progesterone levels 12 hours after the last administration of gonadotropins support the theory that enhanced ovarian stimulation at the end of the follicular phase leads to an overload of the capacity of the enzymes metabolizing progesterone further on, therefore resulting in elevated progesterone levels in circulation.